2022
DOI: 10.1039/d1dt03693a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical design of a new displacive-type ferroelectric

Abstract: Since the discovery of the ferroelectric perovskite-type oxide BaTiO3 in 1943, numerous materials have been surveyed as candidates for new ferroelectrics. Perovskite-type materials have played a leading role in basic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 159 publications
0
12
0
Order By: Relevance
“…The mechanism of the tetragonal-to-cubic phase transition of BaTiO 3 could be explained by an order–disorder model, as shown in Scheme A. On the other hand, the tetragonal-to-cubic phase transition is also achieved when Ti atoms are shifted to the center of the TiO 6 octahedra (i.e., reduction of distortion along the [111] direction). For example, it has been reported that the A-site cation substitution in ABO 3 perovskites induces Ti off-centering due to differences in the ionic size . Furthermore, doping of H – causes a large amount of electron doping at the same time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism of the tetragonal-to-cubic phase transition of BaTiO 3 could be explained by an order–disorder model, as shown in Scheme A. On the other hand, the tetragonal-to-cubic phase transition is also achieved when Ti atoms are shifted to the center of the TiO 6 octahedra (i.e., reduction of distortion along the [111] direction). For example, it has been reported that the A-site cation substitution in ABO 3 perovskites induces Ti off-centering due to differences in the ionic size . Furthermore, doping of H – causes a large amount of electron doping at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported that the A-site cation substitution in ABO 3 perovskites induces Ti off-centering due to differences in the ionic size. 27 Furthermore, doping of H − causes a large amount of electron doping at the same time. As a result, the TiO 6 distortion due to a second-order Jahn−Teller effect will be reduced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perovskite-type ferroelectrics, such as BaTiO 3 , are widely recognized as displacement-type ferroelectrics. 1 These compounds were extensively explored in the 1960s and 1970s, particularly within the soft-phonon mode theory framework. 2 A character-istic feature of these materials is the occurrence of ferroelectric transitions in tandem with crystal tructural transitions.…”
Section: Introductionmentioning
confidence: 99%